Pengaruh E-WOM dan Brand Image terhadap Purchase Intention di Tokopedia: Studi Mahasiswa di Universitas Pembangunan Pancabudi Meda - Salman, Fahd Abdillah; Syahrial, Hery; Sabrina, Hesti (Mahesa Research Center, 2024)
This study aims to determine whether Electronic Word Of Mouth and Brand Image significantly positively influence Purchase Intention in the Tokopedia marketplace. This research uses a Quantitative approach. The population in this study is all students of the Faculty of Social Sciences, Universitas Pembangunan Pancabudi Medan, totaling 4315 students. The sampling technique in this study was conducted by distributing questionnaires to 98 respondents. Electronic Word of Mouth significantly positively affects purchase intention in the Tokopedia marketplace. Brand Image has a significant positive effect on Purchase Intention in the Tokopedia marketplace. Considering that Tokopedia may win the competition with other marketplaces due to respondents' answers indicating that they are not disturbed by negative comments when collecting intentions to buy, it is suggested to maintain the quality by continuously innovating and providing encouragement to consumers to continue to stay on Tokopedia and always choose Tokopedia over other competitors, this has shown that Tokopedia has won the competition among the many existing marketplaces.